A Comparative Analysis of Jigsaw, Team Games Tournament, and Conventional Approaches on Student Achievement in Islamic Religious Education at the Elementary Level - Fitriya, Erma; Saadah, Susi; Kariadinata, Rahayu (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study aims to compare the effectiveness of the Jigsaw, Team Games Tournament (TGT), and conventional learning models in improving Islamic Religious Education learning outcomes in third-grade elementary school students. Using a comparative quantitative research design, this study involved three whole classes, each of which implemented one of these learning models. Student learning outcomes were measured using a standardized assessment instrument after the learning process was implemented. The findings showed clear differences between the three models, with the TGT model producing the highest improvement in learning outcomes, followed by the conventional model, while the Jigsaw model showed the lowest results. These findings indicate that the competitive cooperative learning structure in TGT is able to increase engagement and understanding of religious concepts more effectively than the other two models. This study concludes that the TGT model is superior in supporting the achievement of Islamic Religius Education learning outcomes and has broader pedagogical significance because it can strengthen the cognitive, social, moral, and character-building aspects that are at the core of Islamic education. Therefore, the application of innovative and learner-centered learning strategies needs to be expanded to improve the quality of Islamic Religius Education learning at the elementary school level.